1980
DOI: 10.1017/s0021859600028768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rate, source and distribution method of nitrogen fertilizer on seed potato production

Abstract: Seed potatoes are grown on the high plateaux of northern Israel where it is cool enough for a summer crop. The seed are used for winter production of ware potatoes in southern Israel. Irrigation is essential because of the arid summers. It is customary to apply much of the N fertilizer through the irrigation system in numerous small doses. Total N rates have ranged between 300 and 400 kg/ha. In 1975 various aspects of N, P, K fertilization for seed potato (Solanum tuberosum L., var. Up-ToDate) production were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The sampling of field experiments has usually been too infrequent to establish accurately the time of tuber initiation, but Dyson & Watson (1971) reported that nitrogen slowed the early growth of tubers. Since high rates of nitrogen application stimulate excessive canopy dry-matter production, Baker, Ben Heyuda & Kafkafi (1980) suggested that dividing the application of fertilizer into six equal dressings applied at regular intervals during the season might increase tuber yield by increasing dry-matter partitioning to the tubers. In the present study, withholding half the fertilizer nitrogen until after tuber initiation had no effect on either nitrogen uptake or tuber yield, except when comparing the divided and single applications of 20 g N/m a in 1984.…”
Section: Crop Growth and Tuber Yieldsmentioning
confidence: 99%
“…The sampling of field experiments has usually been too infrequent to establish accurately the time of tuber initiation, but Dyson & Watson (1971) reported that nitrogen slowed the early growth of tubers. Since high rates of nitrogen application stimulate excessive canopy dry-matter production, Baker, Ben Heyuda & Kafkafi (1980) suggested that dividing the application of fertilizer into six equal dressings applied at regular intervals during the season might increase tuber yield by increasing dry-matter partitioning to the tubers. In the present study, withholding half the fertilizer nitrogen until after tuber initiation had no effect on either nitrogen uptake or tuber yield, except when comparing the divided and single applications of 20 g N/m a in 1984.…”
Section: Crop Growth and Tuber Yieldsmentioning
confidence: 99%
“…Millard and Marshall (1986) showed that potato can take up more N than is needed to satisfy immediate requirements for growth. High rates of N application stimulate excessive canopy dry‐matter production (Baker et al, 1980).…”
mentioning
confidence: 99%